China connects the world what behind the belt and road initiative - Wang Yiwei (Beijing China Intercontinental Press & New World Press, 2017)
This book explains the logic concerning globalization, civilization, strategy, economy, politics and diplomacy in an in-depth yet understandable way, and reveals the Chinese wisdom and global wisdom displayed by the Belt and Road Initiative. Based on the history of human civilization and reflection on globalization, it is a monograph on the Belt and Road Initiative after the publication of the same author's The Belt and Road Initiative: What Will China Offer the World in Its Rise one year ago.
Contents -- Preface (recommendation) -- Preface by the author -- Foreword -- Away from the modern times and the western system -- Introduction -- The world looks eastward, China westward : 1. After a millennium, world economic center returns to the east ; 2. A journey to the west 2.0 ; 3. A summary of the belt and road initiative -- Chapter 1 The world is connected : 1. To start : chinized globalization ; 2. To link: connectivity ; 3. To reach: globalized Chinization -- Chapter 2 Belt and road initiative: logic of globalization : 1. Globalization 1.0: mutual learning ; 2. Globalization 2.0: A western-centered world ; 3. Globalization 3.0: an inclusive world -- Chapter 3 Belt and road initiative: logic of civilization : 1. Revival of civilization ; 2. Transformation of civilization ; 3. Innovation of civilization -- Chapter 4 Belt and road initiative: strategic logic : 1. From land-locked to land-crossed ; 2. You do your way, i do my way ; 3. "Longzhong talk" in the 21st century -- Chapter 5 Belt and road initiative: economic logic : 1. Domestic integration ; 2. Double-loop system ; 3. Win-win cooperation -- Chapter 6 Belt and road initiative: political logic : 1. Curve overtaking ; 2. Lane-changing overtaking ; 3. Common revival -- Chapter 7 Belt and road initiative: diplomatic logic : 1. Built of all: community of common interests ; 2. Built by all: community of common responsibility ; 3. Built for all: community of common future -- Chapter 8 Belt and road initiative: perceptive logic : 1. Perceptions and misperceptions of the belt and road initiative ; 2. Ten risks about misperceptions ; 3. Dialectics of the belt and road initiative -- Chapter 9 Chinese wisdom embodied in the belt and road initiative : 1. To start: strategic synergy ; 2. To combine: international cooperation on capacity and equipment manufacturing ; 3. to split: exploring the third-party market -- Chapter 10 Global wisdom embodied in the belt and road initiative : 1. To share: win-winism ; 2. To sustain: balanced development ; 3. To internalize: striking roots -- Conclusion - Postscript -- Appendix: Case Studies -- References
Keywords: China -- Foreign relations -- 21st century; China -- Politics and government